Smart card research and advanced applications : 12th International Conference, CARDIS 2013, Berlin, Germany, November 27-29, 2013. Revised Selected Papers - Rohatgi, Pankaj; Francillon, Aurelien (Lecture Notes in Computer Science, 2014)
This book constitutes the thoroughly refereed post-conference proceedings of the 12th International Conference on Smart Card Research and Advanced Applications, CARDIS 2013, held in Berlin, Germany, in November 2013. The 17 revised full papers presented in this book were carefully reviewed and selected from 47 submissions. The papers are organized in topical sections on security technologies; attacks on masking; side channel attacks; software and protocol analysis; side channel countermeasures; and side channel and fault attacks.